2005
DOI: 10.1002/elps.200410428
|View full text |Cite
|
Sign up to set email alerts
|

Use of a fluorescent phosphoprotein dye to characterize oxidative stress-induced signaling pathway components in macrophage and epithelial cultures exposed to diesel exhaust particle chemicals

Abstract: A large body of evidence has shown that exposure to ambient particulate matter (PM) leads to asthma exacerbation through an excitation of allergic inflammation. Utilizing diesel exhaust particles (DEPs) as a model air pollutant, we and others have demonstrated that PM contains redox-active chemicals that generate inflammation through an oxidative stress mechanism. Recently, the strengths of proteomics have enabled us to demonstrate that organic DEP extracts induce a hierarchical expression pattern of oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 72 publications
0
31
0
Order By: Relevance
“…4C were demonstrated by ProQ diamond staining, which is known as a means of phosphoprotein staining (compare Fig. 4C, ProQ stain with CBB stain) (29). The weak "Pro Q staining" observed for the band of ⌬TM treated with buffer (Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…4C were demonstrated by ProQ diamond staining, which is known as a means of phosphoprotein staining (compare Fig. 4C, ProQ stain with CBB stain) (29). The weak "Pro Q staining" observed for the band of ⌬TM treated with buffer (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Emerin phosphorylated with a Xenopus egg cytosol fraction was separated by 10% gel SDS-PAGE, and the emerin band was excised. Phosphorylation of the protein was detected with ProQ diamond stain (Molecular Probes) according to the manufacturer's instructions and a reference (29).…”
Section: Construction Of Gst-fused Emerin Fragment Proteins and Hismentioning
confidence: 99%
“…Future studies using a proteomics approach (49,50) to identify oxidatively modified proteins in CAPs-exposed macrophages may provide further insights.…”
Section: Discussionmentioning
confidence: 99%
“…While ROS are normal products of aerobic metabolism in cells, under conditions where ROS production increases beyond the ability to detoxify these chemicals, molecular damage may occur. Thus, other studies have shown production of proinflammatory cytokines following DEE exposure (Diaz-Sanchez et al, 1997;DiazSanchez et al, 2000;Wang et al, 2005). DEE may also impact the immune response.…”
Section: Cardiovascular Morbidity-human Panel Studiesmentioning
confidence: 99%